Penerapan Pembelajaran Inquiry Training pada Materi Pokok Listrik Dinamis - Irdes Hidayana Siregar (Gravity Journal, 2022)
This study aims to find out how student activities and the influence of the inquiry training learning model during the learning process. This type of research is quasi-experimental with a two group pretest-posttest design. The population of all class X students of SMA Negeri 1 Padangsidimpuan consists of 5 classes. The research sample was taken by 2 classes which were determined by cluster random sampling technique. The experimental class applies the inquiry training learning model and the control class applies the conventional learning model. The instruments used in this study were observation sheets and learning achievement tests in the form of multiple choice with 5 options. Based on the results of observations, the activity of students in the experimental class was 73.57 (active category) and the control class was 45.09 (very active category). This shows that applying the inquiry training learning model can further enhance student learning activities. After the treatment was carried out in each class, the average post-test score was 75.43 in the experimental class and 64.42 in the control class. The results of hypothesis testing (t test) obtained tcount ttable, namely 4.540 1.66 with α = 0.05. This means that Ha is accepted, in other words there is an effect of applying the inquiry training learning model on student learning outcomes in the subject matter of Dynamic Electricity in class X semester II SMA Negeri 1 Padangsidimpuan T.P. 2021/2022.